Attaining Value from Private Investment in Power Generation Projects in Indonesia: An Empirical Study - Atmo, Gigih; Duffield, Colin; Wilson, David (Universitas Indonesia, 2015)
Provision of electrical infrastructure in emerging economies, like Indonesia, is very challenging post the 2008 Global Financial Crisis (GFC). Constrained lending via international finance markets has led to a reduction in the number of investors and shorter lending periods for public private partnerships (PPPs) projects. While domestic Indonesian investors and banks have begun to be involved in such projects, the scale of budgetary requirements for the delivery of power plant projects generally exceeds the financial capacity of both the public sector and local financial markets. This paper presents the findings of a Delphi style survey and proposes implementation strategies that may overcome current investment constraints and still attain Value for Money (VfM) from the delivery of Indonesian PPP power projects post the 2008 GFC. Initially, qualitative data was acquired from two industry seminars to establish the context of Indonesian PPP power projects. This was followed by two rounds of the Delphi technique to develop consensus among a panel of industry experts about realizing VfM from Indonesian PPPs. The results show that (i) export credit agencies from regional Asian countries have increased their roles to support PPP power projects (ii) structural deficiencies of local power industry manufacturing has created barriers for greater roles of local finances in the projects (iii) enhanced contractual risk allocation between the public and private sector can potentially improve project outcomes; these involve greater transparency and accountability of project guarantee processes. This study adapted key implementation features for attaining VfM into short, medium, and long term development strategies that are suitable for Indonesia. It has been concluded that a sustainable energy system can be realized when there is alignment of interests between the government, project sponsors, fuel suppliers, and lenders.